FAO animal production and health paper N126 - René Perez (FAO, 1997)
After summarizing the principles of energy and protein nutrition, this book presents an extensive review of the research on non-traditional feedstuffs available in the tropics, such as oilseeds, folder tree leaves, aquatic plants, sugar cane, African oil-palm, roots and tubers and organic wastes.